Mediastinal anatomical landmarks, their variants and tips for video‑assisted thoracoscopic navigation during oesophageal extirpation - Dydykin, Sergey; Paulsen, Friedrich; Khorobykh, Tatyana; Mishchenko, Natalya; Kapitonova, Marina; Gupalo, Sergey; Bogoyavlenskaya, Tatyana; Agadzhanov, Vadim; Salikhov, Pashad (Springer-Verlag Italia s.r.l., 2022)
Purpose There is no systematic description of primary anatomical landmarks that allow a surgeon to reliably and safely navigate the superior and posterior mediastinum’s fat tissue spaces near large vessels and nerves during video-assisted endothoracoscopic interventions in the prone position of a patient. Our aim was to develop an algorithm of sequential visual navigation during thoracoscopic extirpation of the esophagus and determine the most permanent topographic and anatomical landmarks allowing safe thoracoscopic dissection of the esophagus in the prone position. Methods The anatomical study of the mediastinal structural features was carried out on 30 human cadavers before and after opening the right pleural cavity. Results For thoracoscopic extirpation of the esophagus in the prone position, anatomical landmarks are defned, their variants are assessed, and an algorithm for their selection is developed, allowing their direct visualization before and after opening the mediastinal pleura. Conclusion The proposed algorithm for topographic and anatomical navigation based on the key anatomical landmarks in the posterior mediastinum provides safe performance of the video-assisted thoracoscopic extirpation of the esophagus in the prone position.